Evaluation of the growth of \(Vibrio natriegens\) strains in a medium containing chitin derivatives and shrimp shell hydrolysate - Le, Tuan; Nguyen, Thanh Hung; Nguyen, Tuan Viet; Vu, Thi Kieu Oanh; Pham, Tuan Anh; Le, Thanh Ha (Academia Journal of Biology, 2023)
Chitin from crustacean waste can be the future substrate for bioindustry towards the circular economy concept, especially for countries having large production of sea products like Vietnam. However, the chemical conversion of chitin into monomers implies high amounts of NaCl in a mixture with glucosamine, N-acetyl glucosamine, and acetate. Thus, a bacterial strain that can tolerate high salt concentration, and use chitin monomers as the sole carbon source such as Vibrio natriegens holds great potential in producing bioproducts from chitin derivatives. In this study, V. natriegens strains 10.3 and N5.3 isolated from Vietnam were compared with the reference strain V. natriegens DSM 759 for their growth performances in medium containing separately glucose and chitin monomers. Strain N5.3 showed the best growth rate among the 3 tested strains, exceptionally in medium containing glucosamine with nearly 1.5 times faster than strains 10.3 and DSM 759. Strain N5.3 cultured in bioreactor at 30 g/L NaCl indicated growth rate ranging from 0.614 to 0.881 h-1 in medium containing glucose, glucosamine, N-acetyl glucosamine, and shrimp shell hydrolysate. The formation of acetate was observed during the exponential growth of strain N5.3 in medium with glucose and N-acetyl glucosamine but not in medium with glucosamine or shrimp shell hydrolysate. The faster growth of all tested strains on N-acetyl glucosamine compared to glucosamine suggested metabolism of these substrates of V. natriegens similar to Eescherichia coli.